Surface modification technologies V proceedings of the Fifth International Conference held in Birmingham, UK, 2-4 September 1991 - Sudarshan, T. S., 1955-; Braza, J. F. (Institute of Materials, 1992)
Topics covered in the 5th International Conference include: orthopaedic implants; diamond and related coatings; vapour deposition; ceramic and optical coatings; laser processing and characterisation; tribological evaluations.
"The meeting was co-sponsored by The Minerals, Metals and Materials Society, the National Science Foundation (USA) and the Federation of European Materials Societies"--Foreword.
Keywords: Surfaces (Technology) -- Congresses.; Coatings -- Congresses.; elektronické knihy; electronic books